Reversing painful and non-painful diabetic neuropathy with the capsaicin 8% patch: Clinical evidence for pain relief and restoration of function via nerve fiber regeneration - Anand, Praveen; Privitera, Rosario; Donatien, Philippe; Fadavi, Hassan; Tesfaye, Solomon; Bravis, Vassiliki; Misra, V. Peter (Frontiers in Neurology, 2022)
Introduction Current oral treatments for pain in diabetic peripheral neuropathy (DPN) do not affect the progression of DPN i.e., “disease modification.” We assessed whether Capsaicin 8% patch treatment can provide pain relief and also restore nerve density and function via nerve regeneration, in both painful (PDPN) and non-painful (NPDPN) diabetic peripheral neuropathy. Methods 50 participants with PDPN were randomized to receive Capsaicin 8% patch Qutenza with Standard of Care (SOC) (PDPN Q+SOC group), or SOC alone (PDPN SOC group). Pain symptoms were assessed with a diary (Numerical Pain Rating Scale, NRPS) and questionnaires. Investigations included quantitative sensory testing (QST) and distal calf skin biopsies, at baseline and 3 months after baseline visit; subsequent options were 3-monthly visits over 1 year. 25 participants with NPDPN had tests at baseline, and 3 months after all received Capsaicin 8% patch treatment. Results At 3 months after baseline, PDPN Q+SOC group had reduction in NPRS score (p = 0.0001), but not PDPN SOC group. Short-Form McGill Pain Questionnaire (SF-MPQ) showed significant reductions in scores for overall and other pain descriptors only in the PDPN Q+SOC group. Warm perception thresholds were significantly improved only in the PDPN Q+SOC group (p = 0.02), and correlated with reduction in SF-MPQ overall pain score (p = 0.04). NPDPN Q+SOC group did not report pain during the entire study. Density of intra-epidermal nerve fibers (IENF) with PGP9.5 was increased at 3 months in PDPN Q+SOC (p = 0.0002) and NPDPN Q+SOC (p = 0.002) groups, but not in the PDPN SOC group. Increased sub-epidermal nerve fibers (SENF) were observed with GAP43 (marker of regenerating nerve fibers) only in PDPN Q+SOC (p = 0.003) and NPDPN Q+SOC (p = 0.0005) groups. Pain relief in the PDPN Q+SOC group was correlated with the increased PGP9.5 IENF (p = 0.0008) and GAP43 (p = 0.004), whereas those with lack of pain relief showed no such increase; in some subjects pain relief and increased nerve fibers persisted over months. PGP9.5 IENF increase correlated with axon-reflex vasodilatation in a NPDPN Q+SOC subset (p = 0.006). Conclusions Capsaicin 8% patch can provide pain relief via nerve regeneration and restoration of function in DPN (disease modification). It may thereby potentially prevent diabetic foot complications, including ulcers.